2017
DOI: 10.1016/j.jqsrt.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of porosity of dust particles on polarization and color with special reference to comets

Abstract: Cosmic dusts are mostly responsible for polarization of the light that we observe from astrophysical objects. They also lead to color-extinction, thermal reemission and other scattering related phenomena. Dusts are made of small particles which are characterised by their size (radius), composition (matter), and structure (morphology, including porosity). In the present work, we address the question of the role of the dust particle porosity on light polarization and color, using Discrete Dipole Approximation (D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Let us add yet another possibility that can enhance Phaethon’s polarization degree: Large surface porosity. It has been numerically confirmed that large porosity significantly increases polarization of material surface 48 , 49 . We also know that this trend holds true regardless of wavelength of incident light 50 , 51 , although its theoretical understanding is not yet completely established, particularly when the wavelength is shorter than the characteristic size of light scatterers on the object surface.…”
Section: Discussionmentioning
confidence: 82%
“…Let us add yet another possibility that can enhance Phaethon’s polarization degree: Large surface porosity. It has been numerically confirmed that large porosity significantly increases polarization of material surface 48 , 49 . We also know that this trend holds true regardless of wavelength of incident light 50 , 51 , although its theoretical understanding is not yet completely established, particularly when the wavelength is shorter than the characteristic size of light scatterers on the object surface.…”
Section: Discussionmentioning
confidence: 82%
“…In laboratory experiments with analog fluffy aggregates, polarizations in the 50%−100% range were measured (Volten et al 2007). In a very recent study, Sen et al (2017) concluded that, over the range in porosity of 0%−50%, p max varies nonmonotonically and can reach or exceed 60%. For a spatially unresolved source, the scattered light can contribute significantly to the total integrated light and associated distance estimates.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown theoretically and through numerical simulations by Sen et al (2017), that a decrease in the colour index is indicative of the increasing presence of finer dust particles while such decrease is not related to change in the particle porosity. Considering a typical size-distribution of the dust particles in the form of an inverse power-law (that is: ∼ 1/a s with the particle radius a), a decrease in the colour index may then be the sign of a larger exponent s. From another point of view, it seems then unlikely to use colourindex data to obtain precise information on the shape and structure (fluffy or compact) of the dust particles.…”
Section: Colour Index and Dust Properties In The Different Coma Regiomentioning
confidence: 99%